Development of a novel electrochemical coagulant dosing unit for water treatment. Issue 1 (12th August 2018) - Llanos, Javier; Isidro, Julia; Sáez, Cristina; Cañizares, Pablo; Rodrigo, Manuel A
Abstract: BACKGROUND: The design of new approaches that help to decrease both the environmental impact of industrial activities and the cost of existing water treatment technologies is becoming a key aspect of research. In the present work, an efficient and easy‐to‐use electrochemical device designed to dose iron coagulants is presented. RESULTS: The proposed device (the Electrochemically‐assisted Coagulant – production & dosing Unit, ECU) exhibits an efficient performance in the dosing of coagulants regardless of the ionic conductivity of the water matrixes tested (within the range 100 to 1000 µS cm −1 ), covering a wide range of potential real surface waters. The behaviour of the ECU device was compared to that of a conventional chemical dosing of iron, and showed better pH (pH ≈ 8 for ECU but < 4 for equivalent chemical dosing) and conductivity (decrease for ECU but increase up to 60% for equivalent chemical dosing) control. Moreover, the ECU unit produced a noticeable amount of Fe 2+ ions, due to the limited access of atmospheric oxygen inside the device. CONLUSION: The device developed overcomes traditional chemical iron dosing and could be potentially applied in uses different from electrocoagulation, as it is the case of Fenton‐related technologies. © 2018 Society of Chemical Industry